2013
DOI: 10.1016/j.actpsy.2013.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing inhibition: How impulsivity and emotional activation interact with different implementation intentions

Abstract: Implementation intentions, a strategy in which a strong link is created between a cue and a to-be-performed action, have been shown to be efficacious in improving self-regulation. The relative efficacy of verbal and visual implementation intentions, however, has yet to be determined. Implementation intentions have also been shown to be inefficacious in participants with high impulsivity, specifically in individuals who reported having a high tendency to commit rash or regrettable actions as a result of intense… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 42 publications
4
12
0
Order By: Relevance
“…They also converge with previous data (e.g., Gollwitzer, 1999), indicating that the efficacy of implementation intentions principally depends on automatic, involuntary processes, as MD had moderate impairments in various laboratory measures of executive functioning, yet benefited from the strategy. In addition, in contrast with the findings of Jessop (2010, 2011), who demonstrated that participants with a high level of urgency (defined as the tendency to experience strong reactions in emotional contexts) did not benefit from implementation intentions, our data corroborate Burkard, Rochat, and Van der Linden's (2013) results that showed that this selfregulation strategy could be efficacious in persons with an elevated level of urgency. This result is of particular importance because urgency has been strongly associated with problematic behaviours, poor functional outcome and caregivers' burden after a TBI (Rebetez, Rochat, Ghisletta, Walder, & Van der Linden, 2015;Rochat, Beni, Billieux, Annoni, & Van der Linden, 2011).…”
Section: Discussionsupporting
confidence: 79%
“…They also converge with previous data (e.g., Gollwitzer, 1999), indicating that the efficacy of implementation intentions principally depends on automatic, involuntary processes, as MD had moderate impairments in various laboratory measures of executive functioning, yet benefited from the strategy. In addition, in contrast with the findings of Jessop (2010, 2011), who demonstrated that participants with a high level of urgency (defined as the tendency to experience strong reactions in emotional contexts) did not benefit from implementation intentions, our data corroborate Burkard, Rochat, and Van der Linden's (2013) results that showed that this selfregulation strategy could be efficacious in persons with an elevated level of urgency. This result is of particular importance because urgency has been strongly associated with problematic behaviours, poor functional outcome and caregivers' burden after a TBI (Rebetez, Rochat, Ghisletta, Walder, & Van der Linden, 2015;Rochat, Beni, Billieux, Annoni, & Van der Linden, 2011).…”
Section: Discussionsupporting
confidence: 79%
“…One possible explanation would be that participants in the current study, confronted with laboratory tasks, did feel less emotionally aroused than participants in Churchill and Jessop's studies, confronted with dieting goals. As mentioned earlier, in a sample of young adults, implementation intentions improved inhibition performances in individuals with high urgency, as long as they were not emotionally aroused (Burkard et al, 2013).…”
Section: Discussionsupporting
confidence: 55%
“…According to Churchill and Jessop (Churchill & Jessop, 2011), the results could be related to the fact that urgency is not defined as difficulty in regulating behavior in general but as difficulty in regulating behavior in the context of negative emotion. Indeed, a study of Burkard, Rochat and Van der Linden (2013) showed that implementation intentions were efficient in individuals with high urgency, as long as they were not emotionally aroused. An alternative hypothesis is that urgency interacts with task difficulty.…”
Section: Moderators Of Implementation Intentions: Urgency and Visualimentioning
confidence: 99%
“…Rather, these real-world situations may benefit from training a more proactive form of IC (as we use here) where one suppresses the motor system before any need arises. Such proactive IC training may be more feasible because participants must consciously apply mental strategies (also known as implementation intentions; see Burkard et al 2013) before overt behavior in a way that is not under speed pressure.…”
Section: Study Novelty and Future Directionsmentioning
confidence: 99%
“…First, it might be more amenable to training than the reactive system, which is very quick, dependent on the speed of detection and signaling via white matter pathways. Second, it is probable that fewer situations in real life require rapid reactive IC; instead, one often has to prepare to suppress a response in advance, and this requires translating goals into action influences, i.e., "implementation intentions" (Burkard et al 2013), which are probably more amenable to training.…”
mentioning
confidence: 99%